Genetic Factors for the Natural Elimination of Hepatitis C Virus - N. V. Vlasenko; T. A. Loscutova; K. O. Mironov; A. S. Esman; E. A. Dunaeva; T. A. Semenenko; D. B. Dubodelov; M. I. Korabelnikova; Z. B. Ponezheva; V. V. Makashova; K. G. Omarova; A. V. Sacuk; et al. (Эпидемиология и вакцинопрофилактика, 2023)
Relevance. The identification of determinants of the human genome, such as single nucleotide polymorphisms (SNPs), in association with various disease patterns, including infectious diseases, is one of the most actively developing areas of scientific research in the world..  Hepatitis C (HC), which remains a serious global health problem, belongs to the number of infections that attract the attention of specialists.Aims. Determination of genetic markers of hepatitis C virus (HCV) natural elimination and assessment of their role as a monitoring parameter of the epidemiological surveillance system.Materials and methods. The study included 660 people divided into 2 groups: persons with chronic HC (CHC) and blood donors (indicator group of the healthy population). In the studied groups, the following SNPs were typed: rs1143634, rs1143627 (IL-1B); rs4251961, rs419598 (IL1RN); rs1800795 (IL6); rs1800896 (IL-10); rs4986790 (TLR4); rs4374383 (MERTK). The associative relationship between SNPs and CHC alleles was identified using logistic regression analysis within four models (codominant, dominant, recessive, and overdominant). Additionally, the significance of polymorphisms at the intragenic and intergenic levels was assessed using modern bioinformatic resources in the field of functional genomics.Results. In this study, genotypes associated with the natural elimination of HCV were identified. Paired combinations of IL 1RA/IL-1B genotypes associated with the probability of the formation of CHC have been established. It is shown that synonymous SNPs can be associated with any characteristics of the pathological process, which can be explained by disequilibrium in coupling with functionally significant alleles of other genetic loci.Conclusion. The detection of the association of SNPs with clinical manifestations of the pathological process is not final and requires further study taking into account ONP coupling groups.